View of the Burgtheater next to the Imperial Riding School in Vienna - Jaresch, Johann, 1786-1840 (engraver):::Creator::::::::::::; Geissler, Maria (publisher):::Contributor:::::::::::: (Vienna; chez Maria Geissler sur le Kohlmarkt; Austria)
Miniature color engraving of the Burgtheater next to the Imperial Riding School